Effect of Psychological Empowerment and Transformational Leadership on Organizational Commitment - Ibrahim, Nurshahira; Ismail, Azman; Mohamed, Nurasilah Kithuru; Salim, Siti Salwa (Makara Human Behavior Studies in Asia, 2015)
According to recent literature that relates to organizational leadership, transformational leadership consists of three important elements: idealized influence, individual consideration and intellectual stimulation. Extant studies in this area highlighted that the ability of the leaders in implementing these transformational processes (to execute organizational functions) may have a significant impact on individual outcome especially organizational commitment. Although this relationship has been studied, the mediating role of transformational leadership has taken a less prominent role in organizational leadership model. Recent studies on organizational leadership have emphasized that transformational leadership has three important characteristics: idealized influence, individual consideration and intellectual stimulation. The purpose of this paper is to examine the influence of empowerment in the relationship between transformational leadership and organizational commitment; by using 77 usable questionnaires gathered from employees who worked at a foreign manufacturing company in Free Trade Zone, Malaysia. Results of SmartPLS path model analysis confirm that empowerment does act as an important mediating variable in the relationship between transformational leadership and organizational commitment in the organizational sample. In the succeeding sections, discussion, implications and conclusion are elaborated.